A DNA insertion/deletion necessitates an aberrant RNA splice accounting for a mu heavy chain disease protein. - Bakhshi, A (1986)
The human heavy chain disease protein BW is an immunoglobulin mu-chain variant whose amino terminus is initiated at the fifth amino acid of the first constant region domain. We cloned and analyzed both rearranged heavy chain alleles from BW leukemic cells to determine the molecular basis for this deleted protein. The phenotypically excluded heavy-chain allele possessed two intermediate recombinations of separate variable-diversity (V-D) and diversity-joining (D-J) junctions, neither of which were expressed. The productive allele, responsible for the mu chain, had a complete V-D-J4 recombination but as a result of a single-base deletion possessed stop codons within the variable region. More important, a small DNA insertion/deletion eliminated the J4 donor splice site. This necessitated an aberrant RNA splice between the leader region and the first constant region domain creating a shortened 2.35-kilobase muRNA. A recognition sequence for signal peptidase predicted a cleavage at the fifth amino acid of the first constant region domain. These molecular events are responsible for the truncated mu chain that lacks a variable region and fails to assemble light chains.